Analysis of the pharmaceutical assistance management situation in a municipality in the interior of Bahia (Research, Society and Development, 2020)
The institutionalization of Pharmaceutical Assistance in primary health care in Brazil, in municipal health systems, is still partial and occurs heterogeneously in different regions of the country. This institutionalization must be guided by the performance of professionals who seek to understand and promote public health policies to manage health services, in an interdisciplinary, intersectoral and multiprofessional perspective that can contribute to the consolidation of the Family Health Strategy. Research with a descriptive, quantitative and exploratory approach of the cross-sectional type, the interviews were carried out in July 2020 with twelve managers of Primary Care, being the Secretary of Health; the Coordinator of the Psychosocial Care Center; the Primary Care Coordinator; the Pharmaceutical Assistance Coordinator; and the managers of the Basic Health Units. This research aimed to report the situation of the PA management and planning capacity, in addition to the identification of possible points of improvement for advancing the service. Dispensing in the units is performed by the nursing technician. All managers know the Municipal List of Medicines, the existence of monitoring and evaluation of care actions is not seen by all managers. Despite advances in Pharmaceutical Assistance across the country and in the municipality studied, there is still much to be done so that problems do not compromise the quality of services.